"There is no alternative" why Margaret Thatcher matters - Berlinski, Claire (New York Basic Books, 2011)
Offers a look at the radical and controversial steps taken by this powerful political figure who transformed a financially weak and ungovernable Great Britain in the 1970s to a rich and influential powerhouse on the world stage via a free-market approach.
Reprint. Originally published: 2008. With a new pref.
UCWS-2014-G-1984 donated by Thomson Reuters
Keywords: Thatcher, Margaret; Conservatism -- Great Britain; Great Britain -- Politics and government -- 1979-1997.